PENGARUH SISTEM KERJA TERHADAP STRESS KERJA DENGAN PENILAIAN MACROERGONOMIC ORGANIZATIONAL QUESTIONNAIRE SURVEY - Simanjuntak, Risma Adelina; -, Rusdianto (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
The compony survive at this point is to create a good work system, from workers point of view, the demans of work and employment components of the existing system may causing many problems to be faced and it can lead to boredom at work. Each componenet to the work system towars level of stress faced by employees. The tools that used to determine the effect of the work system components towards work stress macroergonomics organizational work stress is macroergonomics organizational ques-tionnaire survey and path analysis. It can be seen that simultaneous effect of organi-zational condition employment conditions, physical environments, social enviroment, equipment and technology, and towards work stress experienced by employees amoun-ted to 0.820 and this proves that the influence af all work system components has been investigated is strongly affected the stress of work. While the partial effects of work system components to the stress of work are : organizational conditions amounted to 0,153, the working conditions are 0,166, the physical environment give 0,176 contri-bution, the social environment 0,066, equipment and thecnology amounted to 0,148, and the individual characteristic are to 0,111. So can conclude thet overally, the system components are significantly the work stress.